ANALYSIS OF FAILURES MARINE BOP - Іванків, Ростислав Віталійович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The article analyzed data collected from 83 wells that drilled in the waters of the seas of 400 to 2100 m depth. Working up this information allows to judge about the most unreliable elements of the sea BOP, the impact of deep waters on the reliability of blowout equipment and financial and material coasts that occur in the case failure of the equipment.